Elimination of electrolytic capacitor in AC-DC light emitting diode (LED) driver / Nurul Farhana Aziz - Aziz, Nurul Farhana (2013)
Advance in Light Emitting Diode (LED) lighting system has created a wider application in an effort to improve the conventional lighting system. High demand from customers, including long-lasting, high brightness and reliability system for residential area, heavy industry and even hard and dangerous zone can be solved by replacing the existing lighting system with current LED technology. Nevertheless, while LEDs have almost all other advantages compared to other lighting systems, the existence of electrolytic capacitor in LED driver cause the lifetime of the driver lasted averagely five years while LEDs can stand up to 10 years. This report discuss on the method used to eliminate electrolytic capacitors by replacing the existing driver with fly back converter to produces constant current. In order to obtain a smooth dc output, film capacitor is adopted instead of electrolytic capacitor as a smoothing capacitor. The circuit is designed for 240V ac input and it proposed to the 80W LED which requires 0.7A as the constant output current. The propose topology, detailed design, operation principle of the main circuit and results obtained are presented in this report